The Efectiveness Of The Land optimisation Programme For Enhancing Food Security (SDG 2) in The Village of Kepala Sungai - ANGGI APRILIANI (Journal of Saintech Transfer, 2026)
Food security is a crucial issue currently facing Indonesia and is a goal in sustainable development, namely SDG 2. The Ministry of Agriculture launched the Land Optimization Program (OPLAH) to maintain food sovereignty and fulfill SDG 2. This program aims to increase agricultural land productivity to achieve food sovereignty in Indonesia. This study aims to analyze the implementation of the OPLAH program and analyze the supporting and inhibiting factors. The location of this research was conducted in Kepala Sungai Village, Secanggang District with purposive because this village is one of the recipients of the OPLAH Program. This research employed a qualitative approach with a case study method. Data collection techniques included focus group discussions (FGDs) and interviews with extension workers, the head of the farmer's group (Gapoktan), and the head of groups participating in the OPLAH program in Kepala Sungai Village. The results showed that the OPLAH Program was able to help farmers in improving land and increasing productivity. Supporting factors, consisting of the use of digital technology through WhatsApp groups as a tool for disseminating information in program implementation, the role of extension workers as information disseminators, facilitators, and evaluators, the role of the Gapoktan head as a communicator and motivator. Furthermore, inhibiting factors include the age of the majority of farmers, who are approaching unproductive age, resulting in limited access to information and assistance with poor-quality seeds, resulting in suboptimal cultivation.